Women's Organizations and Democracy in South Africa: Contesting Authority - Hassim, Shireen (Women in Africa and the diaspora / series editors, Stanlie James, Aili Mari Tripp, 2006)
The transition to democracy in South Africa was one of the defining events in twentieth-century political history. The South African women’s movement is one of the most celebrated on the African continent. Shireen Hassim examines interactions between the two as she explores the gendered nature of liberation and regime change. Her work reveals how women’s political organizations both shaped and were shaped by the broader democratic movement. Alternately asserting their political independence and giving precedence to the democratic movement as a whole, women activists proved flexible and remarkably successful in influencing policy. At the same time, their feminism was profoundly shaped by the context of democratic and nationalist ideologies. In reading the last twenty-five years of South African history through a feminist framework, Hassim offers fresh insights into the interactions between civil society, political parties, and the state. Hassim boldly confronts sensitive issues such as the tensions between autonomy and political dependency in feminists’ engagement with the African National Congress (ANC) and other democratic movements, and black-white relations within women’s organizations. She offers a historically informed discussion of the challenges facing feminist activists during a time of nationalist struggle and democratization. Winner, Victoria Schuck Award for best book on women and politics, American Political Science Association “An exceptional study, based on extensive research. . . . Highly recommended.”— Choice “A rich history of women’s organizations in South African . . . . [Hassim] had observed at first hand, and often participated in, much of what she described. She had access to the informants and private archives that so enliven the narrative and enrich the analysis. She provides a finely balanced assessment.”—Gretchen Bauer, African Studies Review